From Ethical Codes to Ethics as Praxis: An Invitation - Kelly Bannister (Ethnobiology Letters, 2018)
Ethical guidance for research involving Indigenous and traditional communities, cultural knowledge, and associated biological resources has evolved significantly over recent decades. Formal guidance for ethnobiological research has been thoughtfully articulated and codified in many helpful ways, including but by no means limited to the Code of Ethics of the International Society of Ethnobiology. We have witnessed a successful and necessary era of “research ethics codification” with ethical awareness raised, fora established for debate and policy development, and new tools evolving to assist us in treating one another as we agree we ought to within the research endeavor. Yet most of us still struggle with ethical dilemmas, conflicts, and differences that arise as part of the inevitable uncertainties and lived realities of our cross-cultural work. Is it time to ask what more (or what else) might we do, to lift the words on a page that describe how we should conduct ourselves, to connecting with the relational intention of those ethical principles and practices in concrete, meaningful ways? How might we discover ethics as relationship and practice while we necessarily aspire to follow adopted ethical codes as prescription? This paper brings together Willie Ermine’s concept of “ethical space” and Darrell Posey’s recognition of the spiritual values of biodiversity with a unique selection of insights from other fields of practice, such as intercultural communication, conflict resolution and martial arts, to invite a new conceptualization of research ethics in ethnobiology as ethical praxis.